Linguistic games, their concept and importance in the educational process - bouras, slimane; chatta, mokrane (El Omda in Linguistics and Discourse Analysis, 2023)
Summary : Language games are one of the modern active methods of teaching language to children, especially, given the psychological intersections between children and the method of providing scientific knowledge. Teaching learning process. What are language games, their types, their history, and their usefulness in making the educational process successful, this is what we seek to answer in this work.